Tenant-Oriented Customized VM Networking Technology - Zirui Zhuang; Jingyu Wang; Tong Xu (Dianxin kexue)
A tenant-oriented customized virtual machine networking system was designed and implemented based on OpenStack.By utilizing metadata definition and template based collaboration，the system implemented automated deployment and control of cloud infrastructures.Features such as unified graphical and draggable tenant interfaces，customized virtual machine networking orchestration，dynamic and batch resource configuration，quality of service control on network interfaces，and a connectivity based optimized mapping algorithm were included.The system provided users ability to configure networks，so that users can manage to conduct virtual machine networking swiftly and without knowledge of underlying technical details.It contributed to reduction of overall virtual networking latency，high efficiency matching of resources and increase in resource utilization.